Andean Culture Values and a Reflection About its Formal Cultivation Through the Eib - Meneses Tutaya, Norma (2018)
Based on a discourse analysis of the interviews carried out with a varied set of people, who identify themselves with the Andean culture, on what are the most important values that serve to determine the integrity of a person, I can conclude that the five fundamental values of the Andean culture, in order of hierarchy, are: industriousness, humility, reliability, reciprocity and solidarity. It should be noted that it is not about the private values of this culture. The final reflection is that all formal education must be oriented to cultivate the cognitive values and principles of the culture of each people that materialize throughout its heritage, that is, to contribute to the fulfillment of the process of enculturation and socialization of the new generations. Since the current Peruvian society is multicultural and multilingual – because tehere are people with different gnoseological-axiological schemes that until now coexist in a conflictive relationship of domination-resistance - it is necessary that the entire formal education system of the country should be intercultural and bilingual.